2022
DOI: 10.3390/biomedicines10112852
|View full text |Cite
|
Sign up to set email alerts
|

Volatilomics as an Emerging Strategy to Determine Potential Biomarkers of Female Infertility: A Pilot Study

Abstract: Due to its high prevalence, infertility has become a prominent public health issue, posing a significant challenge to modern reproductive medicine. Some clinical conditions that lead to female infertility include polycystic ovary syndrome (PCOS), endometriosis, and premature ovarian failure (POF). Follicular fluid (FF) is the biological matrix that has the most contact with the oocyte and can, therefore, be used as a predictor of its quality. Volatilomics has emerged as a non-invasive, straightforward, afforda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 160 publications
(226 reference statements)
0
3
0
Order By: Relevance
“…Volatilomics, a subgroup of metabolomics, focuses on volatile organic compounds (VOCs) that can be derived from both exogenous and endogenous sources (Brinca et al, 2022). VOCs are present in readily accessible biofluids such as urine, exhaled breath, saliva, blood, serum, skin emanations, breast milk, and tissues (Brinca et al, 2022).…”
Section: Vocs In Follicular Fluidmentioning
confidence: 99%
See 1 more Smart Citation
“…Volatilomics, a subgroup of metabolomics, focuses on volatile organic compounds (VOCs) that can be derived from both exogenous and endogenous sources (Brinca et al, 2022). VOCs are present in readily accessible biofluids such as urine, exhaled breath, saliva, blood, serum, skin emanations, breast milk, and tissues (Brinca et al, 2022).…”
Section: Vocs In Follicular Fluidmentioning
confidence: 99%
“…In the context of endometriosis, volatilomics studies have revealed a versatile profile of specific compounds present in follicular fluid. These compounds, such as fatty aldehydes and siloxanes, show altered levels in women with endometriosis compared to controls (Brinca et al, 2022). The presence of these metabolites suggests possible disruptions in steroidogenesis and sphingolipid metabolism, as well as implications in cell signalling and apoptosis (Brinca et al, 2022).…”
Section: Vocs In Follicular Fluidmentioning
confidence: 99%
“…Volatilomics, a subgroup of metabolomics, focuses on volatile organic compounds (VOCs) that can be derived from both exogenous and endogenous sources (Brinca et al, 2022). VOCs are present in readily accessible biofluids such as urine, exhaled breath, saliva, blood, serum, skin emanations, breast milk, and tissues (Brinca et al, 2022). This approach provides insights into the physiological processes of various disorders, including cancer, genetic and metabolic disorders, schizophrenia, and infectious diseases (Longo et al, 2021).…”
Section: Vocs In Follicular Fluidmentioning
confidence: 99%